Treatment compliance in cystic fibrosis patients with chronic Pseudomonas aeruginosa infection treated with tobramycin inhalation powder: The FREE study. (May 2018) - Blasi, Francesco; Carnovale, Vincenzo; Cimino, Giuseppe; Lucidi, Vincenzina; Salvatore, Donatello; Messore, Barbara; Bartezaghi, Marta; Muscianisi, Elisa; Porpiglia, Pasquale Alberto; ,
Abstract: Background: A high treatment burden with nebulised therapies in cystic fibrosis (CF) patients is the major limitation for treatment compliance; moreover, studies on treatment compliance with inhaled antibiotics are limited. This study assessed compliance to TOBI ® Podhaler™ (TIP) treatment in CF patients with chronic Pseudomonas aeruginosa ( Pa ) infections in a real-world setting using the Italian Treatment Adherence CF Questionnaire (ITA-CFq). Methods: This longitudinal, multicentre, cohort study included 2 follow-up (FU) visits: FU-1 at 3-months±15-days from the baseline visit and FU-2 at the end of third TIP cycle (or 6-months after enrolment, whichever occurred first). The effect of TIP on quality-of-life (QoL) and treatment satisfaction were evaluated using Cystic Fibrosis Questionnaire-Revised (CFQ-R) and Treatment Satisfaction Questionnaire for Medication (TSQM), respectively. Overall compliance to treatments was assessed using ITA-CFq. Results: Eighty-two patients (mean age, 24.8 ± 7.9 years), including 22 paediatric patients (age, <18 years), were enrolled in the study; 56 (68.3%) patients, including 17 paediatric patients, completed the study. At baseline, the mean compliance score to aerosol antibiotic treatment was 7.8 ± 3.2; upon introducing TIP, the compliance score improved to 9.4 ± 1.2 at the FU-1 and thereafter remained stable at 9.5 ± 1.2. TSQM was higher for the convenience domain (74.2 ± 17.1 at enrolment and slightly improved to 77.8 ± 15.9 at FU-2) following TIP initiation. No substantial effect of TIP was observed on the QoL when measured using the revised CFQ-R. The safety profile was in line with previous findings. Conclusion: TIP was convenient to use and led to improved treatment adherence in CF patients with chronic Pa- infection. Highlights: Observational, multicentre cohort study in CF patients with P aeruginosa infections. Real-world compliance to TOBI Podhaler was assessed by newly developed ITA-CFq. TIP was convenient to use with improved treatment adherence in CF patients in Italy.